Soroprevalência do SARS-CoV-2 em trabalhadores de hospitais na região Sul de Minas Gerais, Brasil, no ano de 2020 - Caixeta, Duillio Alves (2023)
Determining the seroprevalence of SARS-CoV-2 infection can be performed by detecting anti-SARS-CoV-2 antibodies using immunoassays. The prevalence survey is essential to understand, through estimation, the development and transmission of the disease in the studied population. This study objective to carry out a seroepidemiological survey of SARS-CoV-2 in hospital workers from three cities located in the south of the state of Minas Gerais, Brazil, in 2020. Enzyme-linked immunosorbent assays (ELISA) were performed on sera from 859 participants. The average age was 38 years. Women represented 71.4% and men 28.6%; health professionals were 74.5% and other workers in the administrative sector were 11.6%. The main symptoms reported by the participants were: fever 6.4%, difficulty breathing 5.8%, loss of smell and taste 7.0% and diarrhea 15.8%. 63.35% of the participants also reported contact with infected patients. 21.7% of the individuals presented positive ELISA tests, 62.7% were negative and 15.6% were undetermined. Hospital 3 had the highest positivity rate (22.9%), followed by hospital 2 (21.6%) and hospital 1 (20.3%) (p=0.079). Women had a higher prevalence positivity than men (22.8% and 18.7% respectively). The highest positivity in the test (22.0%) was observed among administrative professionals, followed by health professionals (20.9%). However, professionals who performed laboratory and imaging tests were more positive tests (30.3%), followed by administrative (22.6%), Covid hospital area (22.0%) and non- Covid hospital area (21.5%). A significant correlation was detected between positive ELISA tests and the following variables: previous serological tests, previous contact with infected patients, presence of fever, loss of smell and taste. It is concluded that the ELISA tests were, in the pre-vaccination period, important tools for the detection of antibodies against the virus among hospital professionals. The ELISA tests results showed no significant difference between hospital workers in different areas, nonetheless it demonstrated that hospital professionals in general are exposed to infection. Nevertheless, when analyzing the positive ELISA tests, there was a significant difference between reported symptoms and contact with patients with Covid- 19.